Toward a Shared Urban Transport System Ensuring Passengers & Goods Cohabitation - Trentini, Anna; Mahléné, Nicolas (TeMA - Journal of Land Use, Mobility and Environment, 2010)
The paper presents radical new urban transportation system concepts, potentially allowing changing the economic and environmental costs of passenger and freight transportation. The driver focuses on the concept of sharing, which means to make a joint use of transport resources, between passengers and goods flows. From a field observation of several existing solutions, an inductive reasoning enables us to move from a set of specific facts to establish an archetype for a radical new urban transportation system. Once the archetype defined, it is translated in real life through the example of the On Route proposal for London. The research frame of this paper is the ANR C-Goods (City Goods Operation Optimization using Decision support System) project. Started in February 2009 the project involves four partners , and will end on 2011.